Temperatura da superfície corpórea e perda de calor por convecção em abelhas (Apis mellifera) em uma região semi-árida - Carvalho, Michele Daiana Ferreira de (Universidade Federal Rural do Semi-Árido, 2009)
Honeybees managed in semi-arid region were observed with the objective to determine the individual body surface temperature in different places, as well the heat loss by convection. The body surface temperature was measured with micro thermocouple type T touching in three different body region (the head, thorax and abdomen), its collected from four different places (beehive, hive entrance, foraging and watering place) in which they was arrested by the wings between thumb and forefinger for a few seconds, without causing any injury to the animal. The same time was made measurements of climatic variables. The convective heat transfer was estimated by the theory of convection from a horizontal cylinder. The results showed that had different among temperature surface in parts of the body and in different places. The thorax showed the hottest part of the body, then the head and abdomen was the coldest. In hive entrance the bee had the highest thorax temperature (36.6°C) due the shivering caused for flight muscles. Already, in watering place the surface temperature was the lowest in all parts of the body probably because almost always the body surface had wet by water, if not, at the time of measuring the bee regurgitated the liquid ingest in your body. When the bee was in beehive and in hive entrance (in conditions of low wind) the heat loss by convection increases from 0 to 7.5 W m-2 while increase in the gradient temperature from 0 to 10ºC, but when the wind was 1.0 ms-1 the heat loss by convection increases from 0 to 27.5 W cm-2. In bee hive when the black globe showed a temperature of 43°C, the body surface temperature of bee was 46°C, but when the black globe temperature increased 6°C, the body surface temperature lowered 3°C. These results clearly explain that the bee in a semi-arid region in individual or society has physiological and behavioral mechanisms to regulate their body temperature, but more studies are requires know the most efficient thermoregulatory processes. And climatic variations of the environment are crucially to their thermoregulatory behavior
Body surface temperature and heat loss by convection in honeybees (Apis mellifera) in a Semi-Arid Region
Keywords: Termorregulação; Abelha africanizada; Variáveis climáticas; Semi-Árido Nordestino; Thermoregulation; Body surface temperature; Convection; Honeybee; Semi-arid Region; Abelha; Abelha; CIENCIAS AGRARIAS::MEDICINA VETERINARIA